MATA KULIAH JAPANESE TEACHING DALAM KURIKULUM NON-KEGURUAN - Diah Soelistyowati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2011)
In recent years, Japanese studies in Indonesia has increased greatly, so, it becomes an opportunity for students to develop their competence in the workplace. Therefore, Japanese Teaching is required as to support the curriculum of the Department of Japanese Literature. This is in accordance to the vision and mission of Dian Nuswantoro University.Keywords : Japanese Teaching, Dian Nuswantoro University, curriculum